Precalculus: Mathematics for Calculus, 7th Edition

Published by Brooks Cole
ISBN 10: 1305071751
ISBN 13: 978-1-30507-175-9

Chapter 1 - Section 1.4 - Rational Expressions - 1.4 Exercises: 30

Answer

$x$

Work Step by Step

$\frac{x^2-x-6}{x^2+2x}\times\frac{x^3+x^2}{x^2-2x-3}$ Factorise the fraction $\frac{x^2-x-6}{x^2+2x}$: $=\frac{(x-3)(x+2)}{x(x+2)}$ Simplify the fraction: $=\frac{x-3}{x}$ Factorise the fraction $\frac{x^3+x^2}{x^2-2x-3}$: $=\frac{x^2(x+1)}{(x-3)(x+1)}$ Simplify the fraction: $=\frac{x^2}{(x-3)}$ Multiply the two results: $=\frac{x-3}{x}\times\frac{x^2}{(x-3)}$ $=\frac{x^2(x-3)}{x(x-3)}$ Cancel out $x-3$: $=\frac{x^2}{x}$ Simplify the fraction: $=x$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.